Measurement of jet suppression in central Pb-Pb collisions at √sNN=2.76 TeV - Adam, Jaroslav; Angelov, Venelin; Busch, Oliver; Glässel, Peter; Klein, Jochen; Knichel, Michael Linus; Leardini, Lucia; Lu, Xianguo; Oyama, Ken; Pachmayer, Yvonne C.; Reygers, Klaus; Schicker, Rainer; et al. (Physics letters, 2015)
The transverse momentum (pT) spectrum and nuclear modification factor (RAA) of reconstructed jets in 0-10% and 10-30% central Pb-Pb collisions at sNN=2.76 TeV were measured. Jets were reconstructed using the anti-kT jet algorithm with a resolution parameter of R=0.2 from charged and neutral particles, utilizing the ALICE tracking detectors and Electromagnetic Calorimeter (EMCal). The jet pT spectra are reported in the pseudorapidity interval of |ηjet|<0.5 for 40<pT,jet<120 GeV/c in 0-10% and for 30<pT,jet<100 GeV/c in 10-30% collisions. Reconstructed jets were required to contain a leading charged particle with pT>5 GeV/c to suppress jets constructed from the combinatorial background in Pb-Pb collisions. The leading charged particle requirement applied to jet spectra both in pp and Pb-Pb collisions had a negligible effect on the RAA. The nuclear modification factor RAA was found to be 0.28±0.04 in 0-10% and 0.35±0.04 in 10-30% collisions, independent of pT,jet within the uncertainties of the measurement. The observed suppression is in fair agreement with expectations from two model calculations with different approaches to jet quenching.
*ALICE Collaboration: J. Adam, V. Anguelov, O. Busch, P. Glaessel, J. Klein, M.L. Knichel, L. Leardini, X.G. Lu, K. Oyama, Y. Pachmayer, K. Reygers, R. Schicker, J. Stachel, J. Stiller, M.A. Voelkl, B. Windelband, M. Winn, A. Zimmermann [und 956 weitere Personen]
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Gesehen am 16.07.2021